Identification of Staphylococcus sp. and Antibiotic Resistance in Tutur District, Pasuruan - Purnamasari, Indah; Suwarno, Suwarno; Tyasningsih, Wiwiek (Jurnal Medik Veteriner, 2023)
This study aimed to identify Staphylococcus sp. and antibiotic resistance in Tutur District, Pasuruan. A total of 273 samples of cow's milk were evaluated and identified as Staphylococcus sp. Furthermore, the antibiotic resistance test was carried out according to CLSI standards. This study showed 41 isolates of Staphylococcus sp. of 97 positive CMT. The results of the study reported seven isolates of Staphylococcus sp. resistant to antibiotics consisted of one multidrug-resistant isolate, i.e. S. saprophyticus which was resistant to penicillin, erythromycin and clindamycin, and six antibiotic resistant isolates consisted of two S. aureus isolates, one S. haemolyticus isolate and three isolates S. simulans. Staphylococcus sp. isolates showed resistance to penicillin, erythromycin, clindamycin, and tetracycline. While the antibiotics gentamicin, ciprofloxacin, cefoxitin, and cotrimoxazole did not reported resistance, so these antibiotics were applicable. The incidence of bacterial resistance Staphylococcus sp. to antibiotics with details of resistance to penicillin 7,3%, resistance to tetracycline 7,3%, resistance to clindamycin 4,8% and resistance to erythromycin 4,8%.